Relation between knowledge management and turnover in Slovenian micro and small start-up organisations - Novak, Riko (Organizacija (Kranj), 2013)
This article discusses the importance of knowledge management and employee turnover, using the example of selected Slovenian organisations, in particular, technology parks. The purpose of this article is to point out statistical characteristics between employee turnover and certain selected independent variables. The empirical research was conducted on a population of 667 Slovenian organisations gathered from the subjects of an innovative environment database, and a further sample of 51 chosen technology parks from the A group. By implementing multivariate regression analysis, we sought to examine whether knowledge requirements and knowledge transfer paths in these organisations have a statistically significant influence on employee turnover. The aim of this article is to present the results of empirical research that defines the development of a conceptual framework for understanding the influence of knowledge management on employee turnover. The results have shown that the importance of intellectual and social capital, intangible capital assets and their continuous measurement must be acknowledged within an organisation.
Keywords: management; Slovenia; Slovenija; mala podjetja; zaposleni; kadri; knowledge; znanje; upravljanje